Household Ozone Disinfector as An Alternative Ozone Generator for Ozonolysis of Alkenes. Issue 5 (31st March 2021) - Buntasana, Supanat; Seankongsuk, Pattarakiat; Vilaivan, Tirayut; Padungros, Panuwat
Abstract: Ozonolysis is an oxidative cleavage reaction of alkenes with ozone that is indispensable and has found many applications in organic synthesis. However, dedicated laboratory ozone generators are quite expensive equipment and may not be affordable by many laboratories. Recently, low‐cost ozone disinfectors have become more common as a household appliance. Herein, we demonstrate the applicability of a household ozone disinfector, which can produce ozone in the order of 10 mmol/h, as alternative equipment for the laboratory scale ozonolysis of alkenes. The ozonolysis of 14 styrene derivatives bearing electron‐donating and electron‐withdrawing groups on aromatic rings including those with α‐ and β‐substituents, as well as 8 natural products containing olefinic moieties were investigated. Ozonolysis of these alkenes at millimole scales proceeded to completion within 30–40 minutes and the carbonyl products were obtained in 68% to quantitative yields. Preparative‐scale ozonolysis of 4‐methoxystyrene (6.17 g, 46 mmol) was also demonstrated. The reaction proceeded smoothly to yield 4‐anisaldehyde in 92% yield, which was subsequently converted to p ‐anisaldehyde dimethyl acetal in 66% yield. This work presents household ozone disinfector as an affordable, compact size, and practical synthetic equipment that does not require extra modification. Thus, the household ozone disinfector offers convenient access to ozonolysis or other reactions involving ozone for low‐budget laboratories. Abstract : A low‐cost household ozone disinfector can produce ozone for ozonolysis of alkenes without extra modification. The ozonolysis of 14 styrene derivatives bearing electron‐donating and electron‐withdrawing groups on aromatic rings including those with α‐ and β‐substituents, as well as 8 natural products containing olefinic moieties were performed in good yields. Moreover, the household ozone disinfector was capable of generating ozone for the oxidative cleavage in preparative scales (46 mmol) as demonstrated by the production of p ‐anisaldehyde dimethyl acetal.